2021
DOI: 10.3389/fpls.2021.644904
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Nutrient Cycling and Enrichment of Nutrient-Related Soil Microbes Aid in the Adaptation of Ramie (Boehmeria nivea L.) to Nutrient-Deficient Conditions

Abstract: The breeding for varieties tolerant of adverse growing conditions is critical for sustainable agriculture, especially for ramie (Boehmeria nivea L.). However, a lack of information on the tolerance of ramie to nutrient-deficient conditions has hindered efforts to breed ramie varieties tolerant of such conditions. The main objective of this study was to explore the tolerance strategies of ramie plants under poor soil conditions using long-term (8–9 years) field trials. Genotypes of Duobeiti 1 and Xiangzhu XB we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…The high‐throughput sequencing analysis generally included three steps: DNA extraction, PCR amplification and Illumina MiSeq sequencing. Detailed information on each step can be found in Wu et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The high‐throughput sequencing analysis generally included three steps: DNA extraction, PCR amplification and Illumina MiSeq sequencing. Detailed information on each step can be found in Wu et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Soil microorganisms play a vital role in nutrient recycling [9]. During our previous research, the helpful roles of soil microbes in the adaptation of the ramie to poor soil conditions were confirmed [10]. This is generally achieved through enrichment of the beneficial bacteria and through a reduction of harmful fungi simultaneously.…”
Section: Introductionmentioning
confidence: 81%
“…Phosphate solubilizing microorganisms (PSM) can convert immobilized inorganic P to soluble organic P (i.e., P-solubilization), which increases the bioavailable P for plant uptake and utilization [13]. Our previous work already detected the N-fixing bacteria of Bradyrhizobium from the rhizosphere soil of ramie using sequencing technology [10]. However, the exact N-fixing potential is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in accordance with Bao et al (2019) , who reported that the dominant bacteria in a paddy soil included Bacillus , Acidobacteria/Gp1 , Acidobacteria/Gp3 , and Ktedonobacter . Wu et al (2021) found that the enrichment of beneficial bacteria, mainly Gaiella , contributed to the ability of ramie to tolerate poor soils. Our results showed that the cultivation of different cassava genotypes recruited different unique and core microbes to the cassava tubers and rhizospheres and that the microbes were significantly different in identity and relative abundance ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%